Dreaming of the Future: Reflections of a Latina College Student Receiving DACA Protection in the Trump Era. (April 2022) - Rogers, Jennifer
The Deferred Action for Childhood Arrivals (DACA) program provides legal protection to enhance access for a narrow subcategory of undocumented immigrants. Following the presidential election, a series of actions have pushed many of these recipients into limbo, leading to uncertainty and fear for these young students. This case study examined the intersectional identity and experiences of a first-generation Latina college student who is an undocumented immigrant and has received protection under the DACA program.